2020
DOI: 10.1051/bioconf/20202505008
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Hardy Hibiscus (Hibiscus Moscheutos L.)

Abstract: Hardy hibiscus (Hibiscus x moscheutos L.) is gaining popularity as a landscape plant and the accelerated increase in the volume of planting material is of particular relevance. The work investigated the effect of the concentration of 6-BAP (0.5, 1.0, 1.5 mg / L) on the shoot formation of hibiscus of the following varieties: cv. Cranberry Crush, Fantasia, Fireball, Jazzberry Jam. It was revealed that the concentration of 6-BAP 0.5 mg / L is optimal for the proliferation of microshoots of Hibiscus x moscheutos L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…barnardii explants occurred with an increase in the BAP concentration to 0.75 and 1 mg L -1 (Table 1). Similarly, nodal shoot explants of H. moscheutos cultured on a lower (0.50 mg L -1 ) BAP concentration formed 4.33 shoots per explant compared to three shoots per explant with a higher (1 mg L -1 ) BAP concentration (Lobodina et al, 2020). In contrast, the best bud sprout response (96%) on nodal explants of H. sabdariffa was reported on MS medium supplemented with 1 mg L -1 BAP (Manokari et al, 2016).…”
Section: Bap Concentration and The Type Of Explantmentioning
confidence: 96%
See 4 more Smart Citations
“…barnardii explants occurred with an increase in the BAP concentration to 0.75 and 1 mg L -1 (Table 1). Similarly, nodal shoot explants of H. moscheutos cultured on a lower (0.50 mg L -1 ) BAP concentration formed 4.33 shoots per explant compared to three shoots per explant with a higher (1 mg L -1 ) BAP concentration (Lobodina et al, 2020). In contrast, the best bud sprout response (96%) on nodal explants of H. sabdariffa was reported on MS medium supplemented with 1 mg L -1 BAP (Manokari et al, 2016).…”
Section: Bap Concentration and The Type Of Explantmentioning
confidence: 96%
“…In contrast, Dar et al (2012) reported 88% survival and no contamination of nodal explants of H. rosa-sinensis collected from an outside garden when surface-disinfected with 50% (v/v) Clorox ® [5.25% (w/v) NaOCl] bleach solution containing a higher concentration (2.63%) of NaOCl. In general, however, microbial contaminations of in vitro cultures are found to occur more readily when the explant source is taken directly from field grown plants (Lobodina et al, 2020). Disinfection of nodal explants is considered to be more difficult since the attachment of the petiole to the stem at an angle creates a V-shaped trough wherein contaminants can be trapped, making it more difficult to sterilize nodal explants with axillary buds (Dar et al, 2012).…”
Section: Explant Source and Disinfectionmentioning
confidence: 99%
See 3 more Smart Citations